Recent advances in phytosomes for the safe management of cancer - Abhilasha Singh; Shruti Srivastav; Manjul Pratap Singh; Ranjit Singh; Parveen Kumar; Preeti Kush (Phytomedicine Plus, 2024)
Background: cancer is one of the foremost life-threatening diseases and is managed by various strategies like surgery, radiotherapy, and chemotherapy. Among all, chemotherapy is the most preferential strategy for cancer management but faces certain limitations. Phytochemicals (PCs) have been considered potential chemotherapeutics and chemopreventive agents but their clinical application can be questionable because of their poor bioavailability and stability. Purpose: phytosomes are promising carriers to deliver anticancer PCs to the target site with improved bioavailability and stability owing to their unique properties. This comprehensive review discusses the recent advances in phytosomes loaded with anticancer PCs (covering the period of 2013-December 2023) to overcome the limitations of PCs. Study design and methodology: initially, this review covers the anticancer PCs that are under clinical trials along with the PCs that are FDA-approved (especially for cancer management). Here, we have excluded the PCs that are (a) under an experimental/preclinical or investigational stage; (b) possess activity other than the anticancer; (c) exhibit anticancer activity in combination with other anticancer drugs; and (d) FDA-approved PC-based drugs with activity other than the anticancer. Further, this article mainly emphasizes the clinical application of phytosomes loaded with anticancer PCs to overcome the limitations. Additionally, phytosomes under clinical trials for the management of cancer, their challenges, and future directions are also discussed. Results and conclusion: phytosomes are promising and versatile alternatives to boost the anticancer PCs’ therapeutic efficacy, bioavailability, and specific targeting owing to their distinctive structural composition, which is similar to the composition of cell membranes enabling them close to the physiological systems. Moreover, these vesicular systems can also increase the oral bioavailability of polar PCs, protect them from physical and chemical degradation, and facilitate the targeting efficiency of anticancer PCs through the stimuli-responsive and sustained release of PCs. Therefore, this review will help the researchers to develop a phytochemical-based drug delivery system for the successful management of cancer.